A novel CPT1C variant causes pure hereditary spastic paraplegia with benign clinical course. Issue 3 (4th January 2019) - Hong, Daojun; Cong, Lu; Zhong, Shanshan; Liu, Ling; Xu, Yan; Zhang, Jun
Abstract: Hereditary spastic paraplegia 73 (SPG73) was currently identified in only one family with variant in the neuronal isoform of carnitine palmitoyl‐transferase 1C ( CPT1C ) gene. We described a new family, in which affected individuals exhibited pure hereditary spastic paraplegia with benign clinical course. Exome sequencing revealed a novel nonsense variant in the CPT1C gene. The level of CPT1C mutant transcript significantly decreased compared to that of wild‐type transcript, and can be recovered after cycloheximide administration, which indicated that nonsense‐mediated mRNA decay was a mechanism that might be responsible for the phenotype. Our findings expanded the clinical and genetic spectrum of SPG73.